The Inner Conflict of Iccang as the Main Character in the Uang Panai Tradition: An Analysis of the Film Uang Panai 2 - Nurmadina Nurmadina; Muhammad Taufik Al Makmun; Asti Kurniawati (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study examines the socio-economic issues surrounding the Uang Panai (customary marriage payment) tradition in Makassar, as depicted in the film Uang Panai 2. The tradition requires the groom's side to provide a substantial sum of money regardless of economic circumstances, thereby placing a burden on lower-middle-class families. This situation triggers an internal conflict for the protagonist, Iccang, who serves as the breadwinner in the relationship. The study aims to analyze Iccang's internal conflict through the dynamics of the Id, Ego, and Superego, drawing on Sigmund Freud's psychoanalytic theory. A qualitative descriptive method is employed, utilizing the film Uang Panai 2 as the data source. Data were gathered through repeated observations of scenes and dialogue that reflected the character's internal struggle. The findings reveal that Iccang's conflict stems from his desire to marry his girlfriend, a doctor from a wealthy family. The Id drives him to pursue the marriage, the Ego makes him aware of his financial limitations, and the Superego reflects his consciousness of siri—a concept of honor and self-worth in Bugis-Makassar culture. The clash among these three personality aspects generates anxiety, ultimately prompting Iccang to re-evaluate the meaning of siri and personal dignity within Bugis-Makassar culture.